Preparation method of solid oxide electrolytic cell cathode for ammonia synthesis
By impregnating ruthenium salt in the porous cathode framework and generating Ru nanoparticles through redox treatment, proton-electron hybrid conductive composite cathode is prepared, which solves the problem of catalyst agglomeration caused by high-temperature calcination in traditional methods, and significantly improves the catalytic activity and electrochemical performance of synthetic ammonia.
Patent Information
- Application Number
- CN202311362585.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-18
AI Technical Summary
The traditional Haber-Bosch method requires high temperature and high pressure to produce ammonia, which leads to large energy consumption and serious carbon emissions. The cathode material agglomerates the catalyst particles during the high-temperature calcination process, limiting the reaction activity.
Ru nanoparticles were generated in situ in the porous cathode skeleton by immersion method to prepare proton-electron hybrid conductive composite cathodes loaded with Ru nanoparticles to avoid the high-temperature calcination process and keep the catalyst particles at the nanoscale.
The catalytic activity of synthetic ammonia in solid oxide electrolyte cells is significantly improved, the interface contact between the electrode and the electrolyte is improved, the three-phase interface is increased, the reaction polarization resistance is reduced, and the electron transfer efficiency is improved.
Smart Images

Figure CN119843305A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a cathode of a solid oxide electrolytic cell for synthesizing ammonia, and belongs to the technical field of solid oxide electrolytic cells. Background Art
[0002] Ammonia, as an important inorganic chemical product, is a raw material or intermediate for the manufacture of chemicals such as fertilizers, dyes, and drugs. In addition, the energy density per unit volume of liquid ammonia is 1.5 times that of liquid hydrogen, and the hydrogen storage capacity per unit volume is 1.7 times that of liquid hydrogen. At the same time, in terms of storage and transportation, the conditions for ammonia liquefaction are milder than those for hydrogen liquefaction, and it is an ideal carbon-free fuel and hydrogen carrier. At present, the Haber-Bosch method is mainly used in industry to produce ammonia. This method needs to be carried out under high temperature (400-500°C) and (high pressure 15-25MPa). This process will cause huge energy consumption and serious carbon dioxide emissions. With the increasingly serious energy and environmental crises in recent years, how to efficiently and environmentally friendly realize the synthesis of ammonia and help the development of related industries is a key issue at present.
[0003] Compared with the traditional Haber-Bosch method, the proton conductor solid oxide electrolysis cell can realize nitrogen hydrogenation reduction to generate ammonia at medium temperature. This method does not require a high-pressure environment and the conditions are milder. In addition, the proton source of electrochemical ammonia synthesis is abundant. In addition to hydrogen, water, ethanol, natural gas, etc. can also be used, which avoids the energy consumption caused by the preparation, storage and transportation of hydrogen, and effectively reduces the carbon emissions caused by the entire ammonia synthesis line. In summary, it is considered to be an environmentally friendly preparation method. For solid oxide electrolytic cell ammonia synthesis technology, the cathode materials used in the early stage were mostly pure metal Pd, Ag-Pd, Fe, etc. (Science, 1998, 282 (5386): 98-100; Solid State Ionics, 2007, 178 (1-2): 153-159; Journal of Solid State Electrochemistry, 2005, 9: 201-204.), and later expanded to various perovskite oxides, such as STF, BCYR, etc. (Fuel Processing Technology, 2022, 235: 107380; Journal of Materials Chemistry A, 2022, 10 (46): 24813-24823; Journal of The Electrochemical Society, 2017, 164 (13): F1323.). Compared with pure metal electrodes, the thermal expansion coefficient of perovskite cathodes is more matched with proton conductor electrolytes and has obvious economic advantages. In addition, metal catalysts such as Fe and Ru can be introduced into the perovskite cathode layer, thereby showing considerable catalytic ammonia synthesis activity (Fuel Processing Technology, 2022, 235: 107380; Catalysis Today, 2017, 286: 41-50; Journal of Materials Science, 2017, 52: 2825-2835.). In conventional preparation methods, the cathode will inevitably undergo a high-temperature calcination process of up to 1000°C, which will cause severe agglomeration of catalyst particles, reduce the reaction interface, and limit the improvement of reaction activity. Therefore, optimizing the microstructure and electrocatalytic activity of the cathode material is a key condition for realizing ammonia synthesis in a solid oxide electrolytic cell.
[0004] As an efficient cathode modification method, the impregnation method can introduce uniformly dispersed catalyst particles into the cathode layer by solution impregnation. This method does not go through a high-temperature calcination process, and the catalyst particles can be maintained at the nanoscale (Catalysis Today, 2017, 286: 41-50.). Such precious metal nanoparticles can optimize the microstructure of the cathode layer, provide abundant synthetic ammonia active centers, and improve the synthetic ammonia activity of the cathode. In previous synthetic ammonia research, the impregnation method is usually used to introduce catalyst nanoparticles into the cathode perovskite skeleton of a pure proton conductor. Although such catalyst particles usually have good electronic conductivity, they are affected by the loading, and it is difficult to form a sufficient conductive network in the cathode layer, thereby affecting the electrochemical performance and catalytic activity. Summary of the invention
[0005] The present invention generates Ru nanoparticles in situ in a porous cathode skeleton by an impregnation method to prepare a proton-electron mixed conductive composite cathode loaded with Ru nanoparticles. The use of the proton-electron mixed conductive composite cathode can further improve the interface contact between the electrode and the electrolyte and provide more three-phase interfaces. At the same time, the nanoscale Ru particles will provide an active center for synthesizing ammonia, accelerate the process of charge transfer, and significantly improve the catalytic activity of synthesizing ammonia of traditional perovskite cathode materials.
[0006] The purpose of the present invention is to provide a method for preparing a composite cathode loaded with Ru nanoparticles by solution impregnation, which can improve the synthetic ammonia activity of a proton-conducting solid oxide electrolytic cell and improve the shortcomings of the performance of existing cathode materials.
[0007] According to one aspect of the present application, a method for preparing a cathode of a solid oxide electrolytic cell for synthesizing ammonia is provided, the preparation method comprising the following steps:
[0008] (1) brushing a solid oxide cathode slurry onto one side of a proton conductor electrolyte sheet and calcining I to obtain a porous cathode skeleton;
[0009] (2) applying a drop of an impregnation liquid containing a ruthenium salt onto a porous cathode skeleton, drying, calcining, and reducing to obtain a proton-electron mixed conductive composite cathode loaded with Ru nanoparticles;
[0010] The solid oxide powder in the solid oxide cathode slurry includes a proton conductor material and an electron conductor material.
[0011] Optionally, the mass ratio of the proton conductor material to the electron conductor material is 1:2 to 2:1.
[0012] Optionally, the mass ratio of the proton conductor material to the electron conductor material is independently selected from any value of 1:2, 1:1, 1.5:1, 2:1, or a range between any two of the above values.
[0013] Optionally, the proton conductor material is selected from at least one of BZCY, BZCYYb, BZY, BCY, BCC, BCD, BCGO, LSGM, LBGM, and SCY.
[0014] Optionally, the electronic conductor material is selected from at least one of LSCF, LST, SFM, SSC, LNF, and PCF.
[0015] Optionally, the ruthenium salt is selected from at least one of ruthenium chloride, ruthenium nitrosyl nitrate and ruthenium nitrate.
[0016] Optionally, the concentration of the impregnation solution containing ruthenium salt is 0.1-1 mol / L.
[0017] Optionally, the concentration of the impregnation solution containing ruthenium salt is independently selected from any value among 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L or a range between any two of the above.
[0018] Optionally, the solvent in the impregnation solution containing ruthenium salt is a mixture of water and ethanol, and the volume ratio of water to ethanol is 3:1 to 1:3.
[0019] Optionally, in the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles, the mass of the Ru element accounts for 5 to 40 wt % of the total mass of the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles.
[0020] Optionally, in the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles, the mass of the Ru element accounts for the total mass of the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles, and is independently selected from any value of 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or a range between any two of the above.
[0021] Optionally, the solid oxide cathode slurry is obtained by ball milling a raw material containing solid oxide powder, a pore former and a binder.
[0022] Optionally, the ball milling speed is 100 to 200 rpm, and the ball milling time is 0.5 to 2 h.
[0023] Optionally, the rotation speed of the ball mill is independently selected from any value of 100 rpm, 120 rpm, 150 rpm, 180 rpm, 200 rpm or a range between any two of the above values.
[0024] Optionally, the ball milling time is independently selected from any value among 0.5h, 1h, 1.5h, 2h or a range between any two of the above values.
[0025] Optionally, the pore-forming agent is selected from at least one of starch, carbon powder and graphite.
[0026] Optionally, the binder is selected from at least one of terpineol of ethyl cellulose, methyl cellulose, dioctyl phthalate, and polyvinyl alcohol.
[0027] Optionally, the pore former accounts for 10-30 wt % of the total mass of the solid oxide cathode slurry.
[0028] Optionally, the pore former accounts for the total mass of the solid oxide cathode slurry and is independently selected from any value of 10wt%, 15wt%, 20wt%, 25wt%, 30wt% or a range between any two of the above.
[0029] Optionally, the binder accounts for 40-60 wt % of the total mass of the solid oxide cathode slurry.
[0030] Optionally, the binder accounts for the total mass of the solid oxide cathode slurry and is independently selected from any value of 40wt%, 45wt%, 50wt%, 55wt%, 60wt% or a range between any two of the above.
[0031] Optionally, the proton conductor electrolyte sheet is selected from an anode-supported electrolyte sheet and / or an electrolyte-supported electrolyte sheet.
[0032] Optionally, in the step (1), the temperature of the calcination I is 900 to 1300° C., and the time of the calcination I is 1 to 2 hours.
[0033] Optionally, in the step (1), the temperature of the calcination I is independently selected from any value of 900°C, 1000°C, 1100°C, 1200°C, 1300°C or a range between any two of the above values.
[0034] Optionally, the heating rate of the calcination I is 2 to 5° C. / min.
[0035] Optionally, the heating rate of the calcination I is independently selected from any value of 2°C / min, 3°C / min, 4°C / min, 5°C / min, or a range between any two of the above values.
[0036] Optionally, in the step (2), the temperature of calcining II is 400-700° C., and the time of calcining II is 1-2 hours.
[0037] Optionally, the temperature of the calcination II is independently selected from any value of 400° C., 500° C., 600° C., 700° C., or a range between any two of the above values.
[0038] Optionally, the heating rate of the calcination II is 2 to 5° C. / min.
[0039] Optionally, in step (2), the reduction temperature is 500-700° C., the reduction time is 1-3 hours, and the reduction atmosphere is hydrogen.
[0040] Optionally, the reduction temperature is independently selected from any value of 500° C., 600° C., 700° C., or a range between any two of the above values.
[0041] Optionally, the reduction time is independently selected from any value of 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or a range between any two of the above values.
[0042] Optionally, the temperature rise rate of the reduction is 1 to 5°C / min.
[0043] Optionally, the temperature rise rate of the reduction is independently selected from any value of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or a range between any two of the above values.
[0044] Optionally, in step (2), the drying is vacuum drying, and the drying time is 20 minutes.
[0045] As a specific implementation, the present application is implemented through the following technical solutions:
[0046] Step (1): evenly coating a solid oxide cathode slurry on one side of a proton conductor electrolyte sheet, and sintering at a high temperature to prepare a porous cathode skeleton;
[0047] Step (2): dissolving an appropriate amount of ruthenium salt in a mixed solution of deionized water and ethanol to prepare an impregnation solution of the ruthenium salt;
[0048] Step (3): drop-coating the impregnation solution prepared in step (2) on the porous cathode skeleton prepared in step (1), and vacuum drying;
[0049] Step (4): heating the cathode obtained in step (3) to generate RuO2;
[0050] Step (5): Repeat steps (3) and (4) until the mass of the Ru element accounts for 5 to 40% of the total mass of the cathode layer;
[0051] Step (6): placing the cathode obtained in step (5) in a hydrogen atmosphere, raising the temperature, and reducing the cathode to obtain a proton-electron mixed conductive composite cathode loaded with Ru nanoparticles.
[0052] Optionally, in step (1), the high-temperature calcination process is carried out in an air atmosphere.
[0053] Optionally, in step (4), the heating process is carried out in an air atmosphere.
[0054] The present invention prepares a porous cathode skeleton in advance, disperses ruthenium salt in the porous skeleton by an impregnation method, generates uniformly dispersed ruthenium nanoparticles in situ through redox treatment, and obtains a proton-electron mixed conductive cathode loaded with Ru nanoparticles, which exhibits more significant catalytic activity for synthesizing ammonia.
[0055] The present application prepares a proton-electron mixed conductive composite cathode loaded with Ru catalyst by impregnating a ruthenium salt solution in a porous cathode skeleton, and then generating Ru nanoparticles in situ on the electrode surface through steps such as roasting and reduction. Unlike traditional perovskite electrodes and pure metal electrodes, the use of a proton-electron mixed conductive composite cathode can improve the interfacial contact between the electrode and the electrolyte and increase the three-phase interface. At the same time, the catalyst does not need to be calcined at high temperature (>1000°C) under this method, which avoids severe agglomeration of Ru particles. Nanoscale Ru particles will provide a large number of highly active centers, increase the active sites of the ammonia synthesis reaction, and accelerate the charge transfer process, significantly improving the catalytic activity of ammonia synthesis.
[0056] In this application, "BZCY" refers to BaZr 1-x-y Ce x Y y O 3-δ (x+y<1);
[0057] "BZCYYb" means BaZr 1-x-y-z Ce x Y y Yb z O 3-δ (x+y+z<1);
[0058] "BZY" means BaZr x Y 1-x O 3-δ (x<1);
[0059] "BCY" means BaCe x Y 1-x O 3-δ (x<1);
[0060] "BCC" means BaCe 1-x Ca x O 3-δ(x<1);
[0061] "BCD" means BaCe 1-x Dy x O 3-δ (x<1);
[0062] "BCGO" means BaCe 1-x G x O 3-δ (x<1);
[0063] "LSGM" means La 1-x Sr x Ga 1-y Mg y O 3-δ (x<1,y<1);
[0064] "LBGM" means La 1-x Ba x Ga 1-y Mg y O 3-δ (x<1,y<1);
[0065] "SCY" refers to SrCe 1-x Yb x O 3-δ (x<1).
[0066] "LSCF" means La 1-x Sr x Co 1-y Fe y O 3-δ (x<1,y<1);
[0067] "LST" means La 1-x Sr x TiO 3-δ (x<1);
[0068] "SFM" refers to Sr2Fe 2-x Mo x O 6-δ (x<2);
[0069] "SSC" means Sm 0.5 Sr 0.5 CoO 3-δ ;
[0070] "LNF" refers to LaNi 1-x Fe x O 3-δ (x<1);
[0071] "PCF" means Pr 1-x Cax FeO 3-δ (x<1).
[0072] The beneficial effects of this application include:
[0073] 1) The present application obtains a stable nano-sized precious metal catalyst by impregnation and then oxidation-reduction. This method is simple and easy to implement, and avoids the agglomeration of precious metal catalysts caused by high-temperature calcination (>1000°C). The precious metal catalyst is in full contact with the perovskite cathode material, showing more catalytic active sites;
[0074] 2) Compared with the traditional perovskite cathode, the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles prepared in the present application significantly reduces the polarization resistance of the reaction due to the introduction of ruthenium nanocatalyst, and exhibits higher electron transfer efficiency and catalytic activity;
[0075] 3) The present application uses a mixed material of proton and electron conductors as the cathode skeleton to reduce the use of ruthenium catalyst, saving economic costs while ensuring sufficient three-phase contact interface and conductivity;
[0076] 4) The preparation method of the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles of the present application adopts a solution impregnation method, which can be used to prepare cathode materials loaded with different metals and has great development potential for different reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is a scanning electron microscope image (SEM) of the LSCF-BZCYYb composite cathode loaded with Ru nanoparticles prepared by impregnating ruthenium nitrite in Example 1 of the present application (a, cross-sectional view, scale is 10um; b, cathode honeycomb structure, scale is 1um; c, distribution of Ru particles on the surface of the LSCF-BZCYYb skeleton after reduction, scale is 100nm; d, LSCF-BZCYYb skeleton, scale is 100nm).
[0078] Figure 2 This is the XRD diagram of the LSCF-BZCYYb composite cathode material loaded with Ru nanoparticles prepared by impregnating ruthenium nitrite in Example 1 of the present application.
[0079] Figure 3 This is a graph of the voltammetric characteristics of the LSCF-BZCYYb composite cathode loaded with Ru nanoparticles prepared by impregnating ruthenium nitrite with nitryl in Example 1 of the present application under nitrogen reduction mode (IE).
[0080] Figure 4This is the impedance spectrum (EIS) of the LSCF-BZCYYb composite cathode loaded with Ru nanoparticles prepared by impregnating ruthenium nitrite in Example 1 of the present application under nitrogen reduction mode. DETAILED DESCRIPTION
[0081] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0082] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0083] In the present application, a Shanghai Chenhua CHI 760E electrochemical workstation was used to perform voltammetric and impedance tests, and a JEOL JMS-7800F scanning electron microscope was used to characterize the microstructure of the battery cathode layer (3 kV).
[0084] Embodiment 1:
[0085] 1) LSCF, BZCYYb, potato starch and 6 w / v% polyethyl cellulose terpineol dispersion were mixed in a mass ratio of 3:2:1:4, and ball milled at 100 rpm for 1 h to prepare cathode slurry;
[0086] 2) The cathode slurry prepared in step 1) is evenly brushed on one side of the BZCYYb electrolyte sheet supported by the Ni-BZCYYb anode, dried, placed in an air atmosphere, heated to 1100° C. at a rate of 5° C. / min, and calcined for 2 h to obtain a porous cathode skeleton;
[0087] 3) dissolving 0.1 mol of ruthenium nitrosyl nitrate in 50 mL of deionized water, and adding an equal volume of anhydrous ethanol to prepare a 1 mol / L ruthenium nitrosyl nitrate impregnation solution;
[0088] 4) drip coating 4.5 μL of the ruthenium nitrosyl nitrate impregnation solution prepared in step 3) on the porous cathode skeleton sintered in step 2), vacuum drying for 20 min, then placing the obtained cathode in an air atmosphere, heating to 500° C. at a rate of 2° C. / min, and calcining for 1 h; the mass of the Ru element accounts for 10% of the cathode layer;
[0089] 5) The obtained cathode was placed in a hydrogen atmosphere, heated to 600°C at a rate of 1°C / min, and reduced for 2h to obtain a LSCF-BZCYYb composite cathode loaded with nano-Ru particles.
[0090] like Figure 1 As shown, the cathode skeleton after high temperature sintering presents a continuous porous structure. After being impregnated with ruthenium nitrate nitrate solution and subjected to high temperature oxidation and reduction, the porous cathode skeleton of LSCF-BZCYYb is still clearly visible, and some uniformly dispersed Ru particles with a particle size of 10 to 20 nm appear. Figure 2 The corresponding XRD results show that they are LSCF, BZCYYb and Ru.
[0091] The Ni-BZCYYb / BZCYYb / Ru-LSCF-BZCYYb electrolytic cell prepared in Example 1 was placed at 300, 400, and 500°C for basic electrochemical testing. During the test, 5% hydrogen (95% argon) was passed into the anode at a flow rate of 30 mL / min, and nitrogen was passed into the cathode at a flow rate of 60 mL / min. The anode was used as the counter electrode and reference electrode, and the cathode was used as the working electrode. The voltammetric characteristic curve was collected at a scan rate of 10 mV / s. The results are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the current density of the battery prepared by this method is as high as 144 mA cm at 500 °C. -2 Although the current density decreases with decreasing temperature, it still maintains 10 mA cm at 300 °C. -2 The constant voltage electrochemical impedance spectroscopy was measured at 300, 400, and 500°C in the frequency range of 0.1 Hz to 100 kHz at the open circuit potential. The results are as follows: Figure 4 As shown. The impedance results are consistent with the volt-ampere relationship. At 500°C, the ohmic resistance and polarization resistance are only 5Ω and 90Ω respectively. When the temperature drops to 300°C, they increase to 29Ω and 400Ω respectively. In summary, the electrochemical performance of the battery is good at high temperature. Although it deteriorates slightly with decreasing temperature, it is still sufficient to meet the subsequent electrocatalytic synthesis of ammonia.
[0092] The Ni-BZCYYb / BZCYYb / Ru-LSCF-BZCYYb electrolytic cell prepared in Example 1 was placed at 300, 400, and 500°C, 5% hydrogen (95% argon) anode atmosphere conditions and nitrogen cathode atmosphere conditions, and constant potential tests were performed at -0.1 to -0.6 V. The best yield (400°C, -0.2 V) is shown in Table 1.
[0093] Embodiment 2:
[0094] 1) LST, SCY, potato starch and polyvinyl alcohol were mixed in a mass ratio of 3:2:3:6 and stirred at 150 rpm for 1 h to prepare cathode slurry;
[0095] 2) Take an electrolyte-supported SCY electrolyte sheet, whose anode side is Ni-SCY. Apply cathode slurry on one side of the electrolyte sheet, dry it, place it in air atmosphere, heat it to 1050℃ at a rate of 3℃ / min, and calcine it for 1.5h to obtain a porous cathode skeleton;
[0096] 3) Take 0.025 mol of ruthenium chloride and dissolve it in 25 mL of deionized water, add anhydrous ethanol and mix well to prepare a 0.25 mol / L ruthenium chloride impregnation solution. The volume ratio of deionized water to anhydrous ethanol is 1:3;
[0097] 4) 4 μL of the impregnation solution prepared in step 3) was drop-coated on the porous cathode skeleton sintered in step 2) each time, and vacuum dried for 20 min. The obtained cathode was then placed in an air atmosphere, heated to 400° C. at 5° C. / min, and calcined for 2 h.
[0098] 5) Repeat step 4) until the mass of Ru accounts for 20% of the cathode layer, place the obtained cathode in a hydrogen atmosphere, heat it to 600°C at a rate of 2°C / min, and reduce it for 3h to obtain an LST-SCY composite cathode loaded with Ru nanoparticles.
[0099] The ammonia yield of the prepared Ni-SCY / SCY / Ru-LST-SCY electrolytic cell was measured in the manner of Example 1, and its optimal yield (400°C, -0.2V) is shown in Table 1.
[0100] Embodiment 3:
[0101] 1) LNF, BZCY, potato starch, and 10 w / v% polyethyl cellulose terpineol dispersion were mixed in a mass ratio of 3:6:3:10 and ball-milled at 200 rpm for 0.5 h to prepare cathode slurry;
[0102] 2) Evenly brush on one side of the BZCY electrolyte sheet supported by the Ni-BZCY anode, dry it, place it in an air atmosphere, heat it to 1000°C at a rate of 2°C / min, and calcine it for 3h to obtain a porous cathode skeleton;
[0103] 3) Dissolve 0.05 mol of ruthenium nitrate in 75 mL of deionized water, add anhydrous ethanol and mix well to prepare a 0.5 mol / L ruthenium nitrate impregnation solution. The volume ratio of deionized water to anhydrous ethanol is 3:1;
[0104] 4) 2 μL of the impregnation solution prepared in step 3) was dripped onto the porous cathode skeleton sintered in step 2) each time, and vacuum dried for 20 min. The obtained cathode was then placed in an air atmosphere, heated to 400° C. at a rate of 5° C. / min, and calcined for 1 h.
[0105] 5) repeating step 4) until the mass of Ru accounts for 40% of the cathode layer, then placing the cathode layer in an air atmosphere, heating it to 600° C. at a rate of 5° C. / min, and calcining it for 1 h;
[0106] 6) placing the cathode layer obtained in step 5) in a hydrogen atmosphere, heating it to 700° C. at a rate of 5° C. / min, and reducing it for 3 h to obtain a LNF-BZCY composite cathode loaded with Ru nanoparticles.
[0107] The ammonia yield of the prepared Ni-BZCY / BZCY / Ru-LNF-BZCY electrolytic cell was measured in the manner of Example 1, and its optimal yield (400°C, -0.1V) is shown in Table 1.
[0108] Embodiment 4:
[0109] 1) SFM, BCGO, graphite powder and polyvinyl alcohol were mixed in a mass ratio of 3:2:2:8 and ball milled at 200 rpm for 1 h to prepare cathode slurry;
[0110] 2) Take an electrolyte-supported BCGO electrolyte sheet, whose anode side is Ni-BCGO. Apply cathode slurry on one side of the electrolyte sheet, dry it, place it in air atmosphere, heat it to 1100℃ at a rate of 5℃ / min, and calcine it for 2h to obtain a porous cathode skeleton;
[0111] 3) Dissolve 0.05 mol of ruthenium nitrate in 25 mL of deionized water, add anhydrous ethanol and mix well to prepare a 0.5 mol / L impregnation solution. The volume ratio of deionized water to anhydrous ethanol is 1:3;
[0112] 4) 2 μL of the impregnation solution prepared in step 3) was dripped onto the porous cathode skeleton sintered in step 2) each time, and vacuum dried for 20 min. The obtained cathode was then placed in an air atmosphere, heated to 600° C. at 2° C. / min, and calcined for 1 h.
[0113] 5) Repeat step 4) until the mass of Ru accounts for 10% of the cathode layer, place the obtained cathode in a hydrogen atmosphere, heat it to 600°C at a rate of 5°C / min, and reduce it for 2h to obtain a SFM-BCGO composite cathode loaded with Ru nanoparticles.
[0114] The ammonia yield of the prepared Ni-BCGO / BCGO / Ru-SFM-BCGO electrolytic cell was measured in the manner of Example 1, and its optimal yield (500°C, -0.2V) is shown in Table 1.
[0115] Example 5
[0116] 1) SSC, LSGM, carbon powder and dioctyl phthalate were mixed in a mass ratio of 5:5:2:8 and ball milled at 100 rpm for 2 h to prepare cathode slurry;
[0117] 2) Take an electrolyte-supported LSGM electrolyte sheet, whose anode side is Ni-LSGM. Apply cathode slurry on one side of the electrolyte sheet, dry it, place it in air atmosphere, heat it to 1000℃ at a rate of 5℃ / min, and calcine it for 1h to obtain a porous cathode skeleton;
[0118] 3) Dissolve 0.01 mol of ruthenium nitrate in 50 mL of deionized water, add anhydrous ethanol and mix well to prepare a 0.1 mol / L impregnation solution, where the volume ratio of deionized water to anhydrous ethanol is 1:1;
[0119] 4) 2 μL of the impregnation solution prepared in step 3) was dripped onto the porous cathode skeleton sintered in step 2) each time, and vacuum dried for 20 min. The obtained cathode was then placed in an air atmosphere, heated to 400° C. at 2° C. / min, and calcined for 2 h.
[0120] 5) Repeat step 4) until the mass of Ru accounts for 5% of the cathode layer, place the obtained cathode in a hydrogen atmosphere, heat it to 600°C at a rate of 2°C / min, and reduce it for 2h to obtain a SSC-LSGM composite cathode loaded with Ru nanoparticles.
[0121] The ammonia yield of the prepared Ni-LSGM / LSGM / Ru-SSC-LSGM electrolytic cell was measured in the manner of Example 1, and its optimal yield (500°C, -0.2V) is shown in Table 1.
[0122] Comparative Example 1
[0123] 1) Ru, LSCF, BZCYYb, potato starch and 6 w / v% polyethyl cellulose terpineol dispersion were mixed in a mass ratio of 1:3:2:1:4, and ball milled at 100 rpm for 1 h to prepare cathode slurry;
[0124] 2) The cathode slurry prepared in step 1) is evenly brushed on one side of the BZCYYb electrolyte sheet supported by the Ni-BZCYYb anode, dried, placed in an air atmosphere, heated to 1100° C. at a rate of 5° C. / min, and calcined for 2 h;
[0125] 3) placing the cathode layer obtained in step 2) in a hydrogen atmosphere, heating it to 600° C. at a rate of 1° C. / min, and reducing it for 2 h to obtain a Ru-LSCF-BZCYYb composite cathode.
[0126] The ammonia yield of the prepared Ni-BZCYYb / BZCYYb / Ru-LSCF-BZCYYb electrolytic cell was measured in the manner of Example 1, and its optimal yield (400°C, -0.1V) is shown in Table 1.
[0127] Comparative Example 2
[0128] 1) BZCYYb, potato starch and 6 w / v% polyethyl cellulose terpineol dispersion were mixed in a mass ratio of 5:1:4, and ball milled at 100 rpm for 1 h to prepare cathode slurry;
[0129] 2) The cathode slurry prepared in step 1) is evenly brushed on one side of the BZCYYb electrolyte sheet supported by the Ni-BZCYYb anode, dried and placed in an air atmosphere, heated to 1350° C. at a rate of 5° C. / min, and calcined for 2 h to obtain a porous cathode skeleton;
[0130] 3) dissolving 0.1 mol of ruthenium nitrosyl nitrate in 50 mL of deionized water, and adding an equal volume of anhydrous ethanol to prepare a 1 mol / L ruthenium nitrosyl nitrate impregnation solution;
[0131] 4) dripping 4.5 μL of the impregnation solution prepared in step 3) on the porous cathode skeleton sintered in step 2), vacuum drying for 20 min, then placing the obtained cathode in an air atmosphere, heating to 500° C. at a rate of 2° C. / min, and calcining for 1 h; the mass of the Ru element accounts for 10% of the cathode layer;
[0132] 5) The obtained cathode was placed in a hydrogen atmosphere, heated to 600°C at a rate of 1°C / min, and reduced for 2h to obtain a BZCYYb cathode loaded with Ru nanoparticles.
[0133] The ammonia yield of the prepared Ni-BZCYYb / BZCYYb / Ru-BZCYYb electrolytic cell was measured in the manner of Example 2, and its optimal yield (400°C, -0.2V) is shown in Table 1.
[0134] Table 1 Ammonia synthesis activity of ruthenium cathode catalyst prepared by impregnation method and comparative catalyst activity
[0135]
[0136] It can be seen from Table 1 that the proton-electron mixed conductive composite cathode examples 1 to 5 loaded with ruthenium nanoparticles prepared by the preparation method of the present application all exhibited certain ammonia synthesis activities, and were significantly higher than those of comparative examples 1 and 2.
[0137] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a cathode of a solid oxide electrolytic cell for synthesizing ammonia, characterized in that: The preparation method comprises the following steps: (1) brushing a solid oxide cathode slurry onto one side of a proton conductor electrolyte sheet and calcining I to obtain a porous cathode skeleton; (2) applying a drop of an impregnation liquid containing a ruthenium salt onto a porous cathode skeleton, drying, calcining, and reducing to obtain a proton-electron mixed conductive composite cathode loaded with Ru nanoparticles; The solid oxide powder in the solid oxide cathode slurry includes a proton conductor material and an electron conductor material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the proton conductor material to the electron conductor material is 1:2 to 2:1; Preferably, the proton conductor material is selected from at least one of BZCY, BZCYYb, BZY, BCY, BCC, BCD, BCGO, LSGM, LBGM, and SCY; Preferably, the electronic conductor material is selected from at least one of LSCF, LST, SFM, SSC, LNF and PCF.
3. The preparation method according to claim 1, characterized in that: The ruthenium salt is selected from at least one of ruthenium chloride, ruthenium nitrosyl nitrate and ruthenium nitrate; Preferably, the concentration of the impregnation solution containing ruthenium salt is 0.1 to 1 mol / L; Preferably, the solvent in the impregnation solution containing ruthenium salt is a mixture of water and ethanol, and the volume ratio of water to ethanol is 3:1 to 1:
3.
4. The preparation method according to claim 1, characterized in that: In the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles, the mass of the Ru element accounts for 5-40 wt % of the total mass of the proton-electron mixed conductive composite cathode loaded with Ru nanoparticles.
5. The preparation method according to claim 1, characterized in that: The solid oxide cathode slurry is obtained by ball milling raw materials containing solid oxide powder, pore former and binder; Preferably, the ball milling speed is 100 to 200 rpm, and the ball milling time is 0.5 to 2 h; Preferably, the pore-forming agent is selected from at least one of starch, carbon powder and graphite; Preferably, the binder is selected from at least one of terpineol dispersion of ethyl cellulose, methyl cellulose, dioctyl phthalate, and polyvinyl alcohol; Preferably, the pore former accounts for 10 to 30 wt % of the total mass of the solid oxide cathode slurry; Preferably, the binder accounts for 40-60 wt % of the total mass of the solid oxide cathode slurry.
6. The preparation method according to claim 1, characterized in that: The proton conductor electrolyte sheet is selected from an anode-supported electrolyte sheet and / or an electrolyte-supported electrolyte sheet.
7. The preparation method according to claim 1, characterized in that: In the step (1), the temperature of calcination I is 900-1300° C., and the time of calcination I is 1-2 hours; Preferably, the heating rate of the calcination I is 2-5° C. / min.
8. The preparation method according to claim 1, characterized in that: In the step (2), the temperature of calcining II is 400-700° C., and the time of calcining II is 1-2 hours; Preferably, the heating rate of the calcination II is 2-5° C. / min.
9. The preparation method according to claim 1, characterized in that: In the step (2), the reduction temperature is 500-700° C., the reduction time is 1-3 hours, and the reduction atmosphere is hydrogen; Preferably, the temperature rise rate of the reduction is 1-5°C / min.
10. The preparation method according to claim 1, characterized in that: In the step (2), the drying is vacuum drying, and the drying time is 20 minutes.
Citation Information
Patent Citations
Ruthenium-based catalyst for ammonia synthesis and preparation method and use thereof
CA3075797A1
Method for preparing nanocomposite cathode material of solid oxide fuel cell through impregnation method
CN108461759A
Ruthenium-nickel composite electrode and preparation method thereof, and application of ruthenium-nickel composite electrode
CN110336041A
Nano-catalyst-loaded perovskite composite anode and preparation method and application thereof
CN114243029A